Navigating Artificial Intelligence in Scientific Manuscript Writing: Tips and Traps - Ishan Kumar; Nidhi Yadav; Ashish Verma (Indian Journal of Radiology and Imaging)
It is being increasingly recognized that the strategic use of artificial intelligence (AI) can catalyze the process of manuscript writing. However, it is imperative that we recognize the hidden biases, pitfalls, and disadvantages of relying solely on AI, such as accuracy concerns and the potential erosion of nuanced human insight. With an emphasis on crafting effective prompts and inputs, this article reveals how to navigate the labyrinth of AI capabilities to create a good-quality manuscript. It also addresses the evolving guidelines from various publishers, shedding light on how to “leverage the digital genie” responsibly and ethically. We further explore how and which AI tools can be harnessed for literature reviews, executing statistical analyses, and polishing the language of the manuscript. Providing practical strategies for maximizing AI's benefits, this article underscores the indispensable value of human creativity and critical thinking, stressing that while AI can “streamline the mundane,” the author's insight remains vital for profound intellectual contributions.